Identifikasi Kandungan Radon (Rn-222) pada Bahan Bangunan Batu Bata di Kawasan Aceh Besar - Evi Yufita, Rini Safitri (Jurnal Teori dan Aplikasi Fisika, 2013)
The research about identifying of radon (Rn-222) esposure in a brick manufacture has been done. The aim is to identify the behavior of radon before and after burning in a brick factory in Aceh Besar district. Samples were taken at 6 villages namely Lhiep village, Krueng Anoi, Lamreung, Lambada Peukan, Kleng Cot Arun, and Neuheun. Bricks used as many as 60 pieces of the whole village. Measurement technique using a short-term radon monitoring tools Model 1027 Profetional Countinue Radon Monitor countinue with sampling methods and performed for 12 hours. The results obtained showed that the average value of the highest radon concentration in the bricks before firing from the village Lhiep with 1.80 pCi / l and the lowest in the village of Lambada Peukan of 0.72 pCi / l. In contrast, values obtained after burning an average radon concentration was highest in the village of Lambada Peukan was 0.52 pCi / l and the lowest in the Lhiep of 0.14 pCi / l. High or low radon concentration value on the bricks before burning than influenced than clay soils (clay) used are also expected due to geographical area (upland or lowland), whereas for bricks after firing is influenced by combustion processes that cause cracks in brick so that radon is the brick can come out through the slit bricks. So the bricks are in Aceh Besar district after the test was still relatively low at 2.0 pCi / l and